Antioxidant Test, Total Alkaloid Content, Antimitosis Test and HPTLC Test of Chamomile Flower Extract (Matricaria Chamomilla L.) - Tantowi, Ferdy; Limanan, David (Green Publisher Indonesia, 2023)
Oxygen is one of the supports of multicellular life and is necessary for aerobic metabolism. However, the use of oxygen can produce by-products, one of which is reactive oxygen species (ROS) which can also increase due to external factors such as exposure to ionizing rays, and vehicle smoke. When reactive oxygen species levels are high, the body can experience a condition called oxidative stress, which is a condition that can cause tissue damage. To overcome this, antioxidants are needed, namely compounds that can donate electrons to free radicals to neutralize their effects. Antioxidants are divided into endogenous antioxidants and exogenous antioxidants. Endogenous antioxidants are antioxidants found in the body. Exogenous antioxidants are antioxidants that come from outside the body. Because there is an increase in ROS levels due to external influences, an increase in exogenous antioxidants is needed, one of which is chamomile flowers. This study evaluated qualitative phytochemical levels using the Harnborne method, total antioxidant capacity using the Blois method, total quantitative levels of alkaloids using the Trivedi et al method, BSLT toxicity using the Meyer method, and fingerprint analysis using HPTLC. The obtained chamomile flowers are dried and extracted by maceration using methanol solvent. The test results on chamomile flowers revealed phytochemical content in the form of alkaloids, betasianin, cardioglycosides, coumarins, flavonoids, phenols, quinones, saponins, steroids, tepenoids and tannins. Antioxidant ability 209.27 g/ml; Total alkaloid content of 12.62 g/ml; toxicity 174.39 g/mL; As well as fingerprint analysis chamomile flowers have active ingredients. Therefore, chamomile flowers can serve as a moderate antioxidant with antimitotic activity.